Built Environment and Physical Functioning in Hispanic Elders: The Role of “Eyes on the Street” - Brown, Scott C. (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Research on neighborhood effects increasingly includes the influences of the built environment on health and social well-being. OBJECTIVES: In this population-based study in a low-socioeconomic-status (SES), Hispanic neighborhood, we examined whether architectural features of the built environment theorized to promote direct observations and interactions (e.g., porches, stoops) predicted Hispanic elders’ social support and psychological and physical functioning. METHODS: We coded built-environment features for all 3,857 lots in the 403-block area of an urban Miami, Florida, community. We then conducted three annual assessments of social support, psychological distress, and physical functioning in a population-based sample of 273 low-SES Hispanic elders (70–100 years of age). We used structural equation modeling analytic techniques to examine hypothesized relationships between the built environment and elders’ social support, psychological distress, and physical functioning over a 3-year period. RESULTS: After controlling for age, sex, and income, architectural features of the built environment theorized to facilitate visual and social contact had a significant direct relationship with elders’ physical functioning as measured 3 years later, and an indirect relationship through social support and psychological distress. Further binomial regression analyses suggested that elders living on blocks marked by low levels of positive front entrance features were 2.7 times as likely to have subsequent poor levels of physical functioning, compared with elders living on blocks with a greater number of positive front entrance features [b = 0.99; χ(2) (1 df) = 3.71; p = 0.05; 95% confidence interval, 1.0–7.3]. CONCLUSIONS: Architectural features that facilitate visual and social contacts may be a protective factor for elders’ physical functioning.